MANAJEMEN SENI PERTUNJUKAN “SURYA VISTA ORCHESTRA” DI SEMARANG - Kike De Alfiro (Saraswati)
An orchestral performance management is very important to note the activist music. Where the orchestra is the incorporation of a wide range of instruments that include the type of string instruments, wind instruments, and percussion. In this case, the author raised about management performance of Surya Vista Orchestra. Surya Vista Orchestra stands on 23 January 1999 lead by Paulus Surya in Semarang. The background underlying the formation of a group of Surya Vista Orchestra is as pop music entertainment that can run in the music industry in Indonesia. But in practice the Surya Vista Orchestra can run its business properly and orderly. Writing this paper aims to provide knowledge for students or people who read this paper to find out how to manage a music performance. Management and structure in Surya Vista Orchestra is very simple because the orchestra leader had no formal education about management. In writing this paper is a descriptive study using the method of analysis is qualitative in which describes all valid data and then analyze the performance management of Surya Vista Orchestra. Keywords: orchestra, performance management, Surya Vista Orchestra.